Prospects of Using Spices in Technology Soft-Ripened Goat Cheese - Frolova, Nataliia; Yushchenko, Nataliia; Korolchuk, Irina; Korablova, Olga (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
The problem of balanced nutrition is one of the most important social problems in our time. In the context of changes in population nutrition and protein deficits, increasing attention is being paid to increasing the use of protein resources for nutritional purposes, including the creation of new products. The value of such products is determined not only by the amount of protein, but also by its quality. Goat’s milk is rich in casein and albumin, which contain important amino acids for the human body. Soft-ripened cheese based on goat milk is characterized with high nutrition and biological value, as well as, nutrient availability. Peculiarities of fractional composition of casein of goat milk determine the necessity of searching for methods of adjusting the technological properties of milk during production of cheese. The studies have substantiated feasibility of using spices – turmeric, ginger and fenugreek in the technology of soft-ripened cheese based on goat milk. It is proved, that adding these spices in the dry state with the particles sized up to 0.4 mm to a normalized mixture before thermal conditioning in amount of 1.0 ±0.1 % reduces the indicator of active acidity of normalized mixtures and amount of whey, excreted in the course of processing, by an average of 0.2 рН, provides formation of a more dense clot, speeds up the excretion of whey and increases the product yield by an average of (5.0 ±0.2 %). The formation of a dense clot in the control sample occurred within 60 min, while in the model specimens containing 1% of spices in the dry state – in 45 minutes and hydrated – in 50 minutes. Such a technological effect is apparently associated with adsorption of the components of spices on casein micelle surface and, as a consequence, with reducing their surface potential and subsequent aggregation. The quality indices of goat’s soft cheese made from goat’s milk with spices for at least 5 days at temperature (4 ±2 °С) and relative humidity (85 ±5 %) were established.